Transitions into Older Adulthood by People with Intellectual Disabilities: An Email Conversation - Buell, Susan; Chadwick, Darren (International Journal of Educational and Life Transitions, 2023)
Transitions in older adults with intellectual disabilities are relatively understudied and can operate in ways that differ from typically developing older people. Classification of age and ageing in people with intellectual disabilities has been complex and constructed based upon both traditional ‘typically-developing’ notions of what equates to old age but also age-related changes that can be specific to particular groups of people with intellectual disabilities. There is as wide a range of personality, preference, ability, and lifestyle at different ages within this population as there is in any group without intellectual disabilities. We need a better understanding of later life transitions in this group including the role played by communities and supports. In this article we present a conversation about transitions and the actors that influence transition in adults with intellectual disabilities as they age and enter old age.